A study on epidemiological and clinical characteristics of measles patients admitted to Sir Ronald Ross institute of tropical and communicable diseases, Hyderabad, India - ., Asma; Pulla, Anupama; Thomas, Vimala (International Journal Of Community Medicine And Public Health, 2019)
Background: Measles is an acute infectious exanthematous disease of childhood caused by paramyxovirus. With increase in immunization coverage levels, the intensity of measles outbreak has decreased in the country. In some parts of India, measles is still a major cause of morbidity and childhood mortality. Objective of the study was to determine the epidemiological and clinical characteristics of patients with macular/maculo-papular rash. Methods: A cross sectional record based retrospective study was carried out at Sir Ronald Ross institute of tropical and communicable diseases, Hyderabad. All the cases admitted in year 2016 with history of fever and macular/maculo-papular rash were included in the study. The study was carried out for 2 months. Results: A total of 639 cases were admitted to infectious disease hospital during the year 2016 with history of fever and rash. The mean age of study population was 6.08±4.9 years. Around 43.7% of cases were in the age group of 1–5 years. The disease was slightly higher among boys (52.3%) as compared to girls (47.7%). Amongst the clinical features, fever and rash were seen in 100%, coryza in 80%, and conjunctivitis in 63.3% of study population. Conclusions: Majority of the children suffering from measles was not vaccinated and the most common reason for failure to immunize children was lack of awareness. There is a need to increase awareness about importance of measles immunization to reduce under five mortality.